Pengaruh Viral Marketing, Online Consumer Review, dan Live Streaming terhadap Keputusan Pembelian Produk Skincare Somethinc pada Platform Tiktok - Sabila, Aminda Khurin; Lazuardy, Ilman Taufiq (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
This research aims to analyze the influence of Viral Marketing, Online Consumer Reviews and Live Streaming on the Tiktok platform. This research uses quantitative methods. The type of research data used is primary data obtained based on distributing questionnaires to 107 respondents. The sampling used used non-probability with a purposive sampling technique with the criteria being that consumers had made at least two purchases in this research. The data analysis method was carried out using multiple linear regression analysis. The test results show that the Viral Marketing, Online Consumer Review and Live Streaming variables have a positive influence on purchasing decisions for Skincare Something on the Tiktok Platform.